2022
DOI: 10.1126/sciadv.abo4856
|View full text |Cite
|
Sign up to set email alerts
|

Geological, multispectral, and meteorological imaging results from the Mars 2020 Perseverance rover in Jezero crater

Abstract: Perseverance’s Mastcam-Z instrument provides high-resolution stereo and multispectral images with a unique combination of spatial resolution, spatial coverage, and wavelength coverage along the rover’s traverse in Jezero crater, Mars. Images reveal rocks consistent with an igneous (including volcanic and/or volcaniclastic) and/or impactite origin and limited aqueous alteration, including polygonally fractured rocks with weathered coatings; massive boulder-forming bedrock consisting of mafic silicates, ferric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…The daily OD evolution was also retrieved from TIRS infrared measurements, strengthening the case for night-time clouds. Figure 4e shows the diurnal variation of thermal infrared aerosol OD, contributed Values are observed to be higher in the morning than in the afternoon, consistent with measurements made occasionally with MastCam-Z 22 . b, RDS observations also allow the derivation of the OD at a temporal resolution of 1 s, enabling the study of short-duration events, such as DD.…”
Section: Atmospheric Dust Propertiessupporting
confidence: 79%
See 2 more Smart Citations
“…The daily OD evolution was also retrieved from TIRS infrared measurements, strengthening the case for night-time clouds. Figure 4e shows the diurnal variation of thermal infrared aerosol OD, contributed Values are observed to be higher in the morning than in the afternoon, consistent with measurements made occasionally with MastCam-Z 22 . b, RDS observations also allow the derivation of the OD at a temporal resolution of 1 s, enabling the study of short-duration events, such as DD.…”
Section: Atmospheric Dust Propertiessupporting
confidence: 79%
“…4a, including the Article https://doi.org/10.1038/s41561-022-01084-0 increase around sol 70 and most of the morning-afternoon difference, is due to water-ice hazes 36,37 . Clouds were observed around sols 70 and 180, but discrete clouds were not typically present during daytime 22 . During this season, a low dust OD (0.3-0.6), with low variability, is typical of other sites 38,39 .…”
Section: Atmospheric Dust Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Mars 2020 has detected a rich dynamic atmosphere and aeolian environment in Jezero crater with dust lifting mainly produced by the passage of convective vortices and convection cells (Bell et al., 2022; Newman et al., 2022). Measurements obtained during the first few sols of the mission suggested that wind patterns are mainly controlled by regional and local slope flows in accordance with pre‐landing model simulations (e.g., Newman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ventifact formation in the current era might occur only during anomalous weather conditions, e.g., rare strong, sanddriving wind events from atypical directions, associated with dust storms or other unusual weather phenomena. Alternatively, ventifact orientations might indicate a paleowind regime different from the current prevailing conditions (Newman et al, 2022;Bell et al, 2022).…”
Section: Ventifact Orientation Resultsmentioning
confidence: 99%